Perinatal colonization with extended-spectrum beta-lactamase-producing and carbapenem-resistant gram-negative bacteria among home births in Bangladesh - Gregory S. Wu; Hafsa Hossain; Mohammed Badrul Amin; Shahana Parveen; Mohammad Aminul Islam; Ajrin Sultana Sraboni; Abu Faisal Md. Pervez; Dilruba Zeba; Emily S. Gurley; Stephen Luby; Ashley Styczynski (PLoS ONE, 2025)
Background Neonatal infections are increasingly caused by antibiotic-resistant bacteria. It is unknown to what extent home-based births, which account for nearly a third of deliveries in Bangladesh, may also result in exposure to antibiotic-resistant bacteria. Methods We enrolled mothers who delivered at home and their newborns from a rural community in Bangladesh during April-June, 2022. Within 2–7 days after delivery, we collected vaginal and rectal swabs from mothers and rectal swabs from the newborns. Swabs were cultured on chromogenic culture media selective for extended-spectrum β-lactamase-producing bacteria (ESBL-PB) and carbapenem-resistant bacteria (CRB). Demographic and risk factor data were collected via surveys. Birth attendants who facilitated the deliveries were interviewed regarding infection prevention practices. We performed descriptive analyses and Firth’s penalized logistic regression to identify potential risk factors associated with colonization. Results Of the 50 mothers enrolled, the median age was 23 years (range 18–26). Thirty-eight (76%) mothers had at least one antenatal care visit. Only one mother reported hospitalization during pregnancy, and 4 reported antibiotic use during pregnancy. Following delivery, 47 (94%) mothers were colonized with ESBL-PB, and 37 (74%) were colonized with CRB. Of the newborns, 36 (72%) were colonized with ESBL-PB, and 27 (54%) were colonized with CRB. No associations were found with any perinatal exposures, though all households reported incomes below the international poverty level. Of the 9 birth attendants who were able to be interviewed, 7 (78%) reported performing hand hygiene before delivery, and 8 (89%) reported glove use during delivery. Attendants reported cleaning equipment shared across deliveries with soap and water and using boiled water for delivery (89%, n = 8). Conclusions Women and newborns in this rural population were frequently colonized with both ESBL-PB and CRB following home deliveries. This demonstrates the importance of community-based antibiotic-resistant bacterial transmission and need for further understanding community exposures driving antibiotic resistance.